Inovasi Teknologi Finansial dalam Manajemen Risiko pada Lembaga Keuangan Syariah: Studi Kasus di Baznas Microfinance Desa Kota Malang Aplikasi Akuntansi UMKM - Ismi Nur Aisyah; Nur Hayati (Jurnal Akuntansi dan Bisnis Syariah, 2024)
All this research aims to analyze the implementation of accounting applications in risk management at Baznas Microfinance in Desa Kota Malang. The primary focus is to explore how financial technology can enhance risk management, operational efficiency, and customer satisfaction within the framework of Islamic financial institutions. The study employs a qualitative approach, utilizing in-depth interviews and direct observations as the primary data collection techniques. Key informants include managers, staff of Baznas Microfinance, and customers who utilize its services. The gathered data is analyzed thematically to identify emerging patterns and themes from the interviews and observations. Findings indicate that the application of accounting software has a significant positive impact on risk management. Firstly, there is an increase in transparency and accountability, which aids in minimizing errors and fraudulent activities in transaction recording. Respondents reported that the application facilitates the preparation of accurate and easily accessible financial reports. Secondly, operational efficiency has improved, with staff noting that recording and reporting processes have become significantly quicker. Lastly, customer satisfaction has increased due to faster and more transparent services, leading to enhanced trust in the institution. In conclusion, this study asserts that the adoption of financial technology, particularly accounting applications, serves as an effective solution for improving risk management in Islamic financial institutions such as Baznas Microfinance. The findings contribute to the literature on financial technology's role in enhancing the operational capabilities and customer relations of microfinance institutions.